The practice of sustainable home cooking – a fascinating philosophical perspective - Salgado, Diana; Verkerk, Maarten J. (Frontiers in Sustainable Food Systems, 2022)
Introduction In this article we explore the practice of sustainable home cooking from a philosophical perspective. Methodology We analyze the practice of sustainble homecooking on the basis of the theory of modal aspects (Dooyeweerd) and the Triple I model (Verkerk and others). Results and discussion Philosophy offers a fascinating perspective on sustainable home cooking. First, it shows the richtness of the phenomenon of home cooking. Second, it shows that home cooking constists out of two sub practices: preparing a meal and eating a dish. Each of these sub practices has an own identity and own inherent values. Third, the transition to sustainable home cooking requires three related strategies. (1) A transition of present home cooking practices to a sustainable practice by focussing on the inherent values of sustainable home cooking. (2) A transition of the whole food chain to a sustainable one. (3) A transition in the ideals and basic beliefs of society about sustainable home cooking.